Single and mixed poloxamine micelles as nanocarriers for solubilization and sustained release of ethoxzolamide for topical glaucoma therapy - Ribeiro, Andreza (2012)
Polymeric micelles of single and mixed poloxamines (Tetronic) were evaluated regarding their ability to host the antiglaucoma agent ethoxzolamide (ETOX) for topical ocular application. Three highly hydrophilic varieties of poloxamine (T908, T1107 and T1307) and a medium hydrophilic variety (T904), possessing a similar number of propylene oxide units but different contents in ethylene oxide, were chosen for the study. The critical micellar concentration and the cloud point of mixed micelles in 0.9 per cent NaCl were slightly greater than the values predicted from the additive rule, suggesting that the co-micellization is hindered. Micellar size ranged between 17 and 120 nm and it was not altered after the loading of ETOX (2.7-11.5 mg drug g-1 poloxamine). Drug solubilization ability ranked in the order: T904 (50-fold increase in the apparent solubility) > T1107 ≅ T1307 > T908. Mixed micelles showed an intermediate capability to host ETOX but a greater physical stability, maintaining almost 100 per cent drug solubilized after 28 days. Furthermore, the different structural features of poloxamines and their combination in mixed micelles enabled the tuning of drug release profiles, sustaining the release in the 1-5 days range. These findings together with promising hen's egg test-chorioallantoic membrane biocompatibility tests make poloxamine micelles promising nanocarriers for carbonic anhydrase inhibitors in the treatment of glaucoma.